Dual Gate Tunable and High Responsivity Graphene‐Based Field Effect Transistors. Issue 1 (November 2015) - Soni, Mahesh; Sharma, Satinder Kumar; Soni, Ajay
Summary: The output characteristics of a dual gated depletion mode, n‐ channel graphene field effect transistor ( n ‐Gr‐FET) are simulated to understand the unipolar Ids – Vds behavior for different values of gate voltages, ( V back and V top ). In our results, the saturated drain‐source current ( Ids ) varies from 0.001 to 100 µA/µm, 9 to 125 µA/µm and 16 to 135 µA/µm as V back is varied from 5 to 40 V with correspondingly V top of 0, 2 and 10 volts. Consequently, there is four to eight times enhancement in estimated mobility for varying V back from 5 to 40V. The unipolar saturation in Ids at higher values of Vds can be understood from the compensation of parallel Vds and transverse ( V back − V top ) electric fields. Furthermore, the channel length modulation (increase in Ids for V top > 0) supported by the increase in mobility, is observed because of reverse junction formation at the vicinity of the drain and gate terminal. The results signify that the dual gated n‐ Gr‐FET, at optimum V back, modulates the unipolar characteristics in channel region. Thus, making n‐ Gr‐FET a potential candidate to stipulate the demand of low power, high performance functionalities in nano‐electronic applications.